Like Mother, like Child? The Rise of Women's Intergenerational Income Persistence in Sweden and the United States - Gunnar Brandén; Martin Nybom; Kelly Vosters (Institute of Labor Economics (IZA), 2023)
We show how intergenerational mobility has evolved over time in Sweden and the United States since 1985, focusing on prime-age labor incomes of both men and women. Income persistence involving women (daughters and/or mothers) has risen substantially over recent decades in both Sweden and the US, while the more predominantly studied father-son measures remained roughly stable. Interestingly, mother-son and mother-daughter persistence levels are very similar as they rise through the sample period, also to nearly the same levels in both countries, contrary to well-established elevated levels of persistence in the US relative to Sweden. We develop a model to quantify the relative roles of parent human capital, employment, and (residual) income, as well as assortative mating. Despite very similar trends and levels for mothers in the US and Sweden, we find substantial differences in the roles of employment and assortative mating over time, consistent with the staggered timing in women's spike in labor force attachment. Parental assortative mating is also an important factor in both countries, though negative sorting on (residual) income in the US negates the upward influence of positive human capital sorting, lending to the similar cross-country levels of mother-child persistence.
Keywords: J62; J12; J16; J24; 330; intergenerational mobility; gender; inequality